Guilleminea densa (Amaranthaceae): a new record for the brazilian flora - Cunha, Lucas Gonçalves da (2025)
This paper presents the first record of Guilleminea densa for Brazil. Until now, the genus Guilleminea was only represented in Brazil by G. fragilis Pedersen, found in Mato Grosso do Sul. Guilleminea densa is native to most of South America and part of North America and has been recorded as invasive in southern Africa. This species can be easily identified by its glabrous leaves on the adaxial face and densely woolly on the abaxial face, with a dense inflorescence of whitish and woolly flowers. The species was recognized during a floristic survey of ruderal species in the municipality of Santa Maria, in the central region of Rio Grande do Sul, Brazil, where it was found in an urbanized environment. The paper provides descriptions, illustrations, and information on habitat, distribution, and taxonomy.